Implementation of Problem Based Learning on Critical Thinking to Increase Learning Outcomes and Student Activities - Ramadhana, Gery Haris; Sutiani, Ani (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
Learning is required to always be creative in presenting learning materials such as using learning models that can foster student™s enthusiasm in participating  learning process, so that students are happy and interested in exploring the lesson in the hope that their learning outcomes will be better. This study aims to (1) determine the increase in student learning outcomes taught with the Problem Based Learning model based on critical thinking is higher than the Direct Instruction model (2) to find out whether there is an influence of the Problem Based Learning model based on critical thinking on learning activities students on acid base material. From the results of the study, it was found that student learning outcomes in the experimental class were 77%, while those in the control class were 62%. The result of the difference in increasing learning outcomes between the two classes is 15%. From the t distribution data obtained t-table = 1.676 while based on calculations obtained price tcount = 3.73 means that Ho is rejected and Ha is accepted, based on this analysis means there is an influence of the Problem Based Learning model Learning based on critical thinking towards student learning activities on Acid-Base material.Pembelajaran dituntut untuk selalu kreatif dalam menyajikan materi pembelajaran seperti menggunakan model pembelajaran yang dapat menumbuhkan semangat siswa dalam mengikuti proses pembelajaran, sehingga siswa senang dan tertarik untuk mendalami pelajaran dengan harapan hasil belajarnya menjadi lebih baik. Penelitian ini bertujuan untuk (1) mengetahui peningkatan hasil belajar siswa yang diajar dengan model Problem Based Learning berbasis berpikir kritis lebih tinggi daripada model Direct Instruction (2) untuk mengetahui apakah ada pengaruh model Pembelajaran Berbasis Masalah berbasis terhadap berpikir kritis pada kegiatan belajar siswa pada materi asam basa. Dari hasil penelitian diketahui bahwa hasil belajar siswa pada kelas eksperimen sebesar 77%, sedangkan pada kelas kontrol sebesar 62%. Hasil selisih peningkatan hasil belajar antara kedua kelas sebesar 15%. Dari data distribusi t diperoleh t-tabel = 1,676 sedangkan berdasarkan perhitungan diperoleh harga thitung = 3,73 artinya Ho ditolak dan Ha diterima, berdasarkan analisis ini berarti ada pengaruh model pembelajaran Problem Based Learning berbasis berpikir kritis terhadap kegiatan belajar siswa pada materi Asam-Basa.